PHONOLOGIC REPRESENTATION AND SPEECH PERCEPTION: THE ROLE OF PAUSE - Soncin, Geovana [UNESP] (2019)
We investigate the perception of pauses at intonational phrase (IP) boundaries in Brazilian Portuguese (BP) and address the discussion about the relation between speech production and perception. Twenty adult subjects who were native speakers of BP, with no language disorders and no hearing complaints, took part in an experimental pause identification test. We used auditory stimuli in which the IP-boundary was marked by a combination of pause and pitch variation or pitch variation only. The results are as follows: (i) when stimuli consisted of a combination of pause with pitch variation at the IP-boundary, the pauses were significantly identified; (ii) when the stimuli did not have pitch variation at IP boundaries, the pauses were not significantly identified; and (iii) when only pitch variation occurred, without pause production, the pauses were identified at the tested boundary. These results support the argument that speech perception does not entirely depend on recovering an acoustic pattern and provide evidence of the importance of phonologic representation for the perception and organization of the perceived auditory stimulus. Based on the results, we argue that pause perception results from a perceptual illusion marked by the combination of different types of linguistic information at a phonetic-acoustic and representational level.